Age-Related Decrease in the Schaffer Collateral-Evoked EPSP in Awake, Freely, Behaving Rats. Issue 3 (2000) - Barnes, C. A.; Rao, G.; Orr, G.
Abstract : Synaptic response size in the CA1 region of the hippocampus in aged rats is reduced for a given stimulus intensity, compared with that elicited in young rats. Consistent with the in vitro findings of reduced Schaffer collateral-evoked CA1 EPSPs in old rats, the population currents evoked to iontophoretically applied AMPA are also smaller relative to the presynaptic fiber potential amplitude. On the other hand, the size of the presynaptic fiber potential and amplitude of unitary intra-cellularly recorded EPSP responses do not change across age in the CA1 region. These electrophysiological findings are consistent with the hypothesis that old rats have fewer functional synaptic contacts per Schaffer collateral axon than do young rats. The possibility that this age change arises as a result of a differential tissue recovery response to in vitro preparation was examined in the present study. CA1 presynaptic fiber potential and EPSP amplitudes evoked by the stimulation of Schaffer collateral afferents were studied in intact, freely behaving young and old rats. We confirmed in vivo the pattern of electrophysiophysiological results previously reported in vitro and found significant correlations between the synaptic response amplitudes and the accuracy of spatial behavior in the Morris swim task. The data suggest that changes in functional connectivity of old rats may be a significant contributor to cognitive changes during aging.